Determinants of Consumption Value on Intention to Use Shariah Mobile Banking: Exploring the Role of Consumer Preference - Maksum, Maksum; Haryono, Slamet (Journal of Finance and Islamic Banking, 2024)
This study analyzes the use of mobile banking by both Islamic and conventional bank customers using the theory of consumption value. The aim of this research is to evaluate the factors influencing customers' decisions to use dual mobile banking services. The proposed hypothesis is that the intention to use Islamic mobile banking services is influenced by functional, conditional, social, emotional, and epistemic values mediated by consumer preferences. The method used is structural equation modeling with partial least squares (SEM-PLS) with a sample of 191 people, all of whom use both conventional and Islamic mobile banking. The results show that the theory of consumption value does not directly affect the interest in using mobile banking, either conventional or Islamic, except for the emotional value variable. Consumer preferences mediate the effect of functional, conditional, emotional, and epistemic values on the intention to use conventional mobile banking. Meanwhile, conditional, emotional, and epistemic values influence the interest in using Islamic mobile banking, which is mediated by consumer preferences. These findings indicate that the consumer's intention to use mobile banking is influenced by the theory of consumption value regardless of whether the service is Islamic or not. The implication of this research is that Islamic mobile banking services need to improve their service quality by considering consumer preferences and the theory of consumption value, thereby enhancing the usage of services by both conventional and Islamic bank customers.